The Saints of Progress: A History of Coffee, Migration, and Costa Rican National Identity - Kordick, Carmen (The University of Alabama Press, 2019)
"This work narrates the development of a historically remote–although internationally celebrated–coffee-growing region from the early 19th century through to the first decade of the 21st century. It considers the nation-building process from the margins to question traditional scholarly works that have reproduced, rather than deconstructed, Costa Rica's exceptionalist national mythologies that imagine this isthmian republic as Central America's 'white,' democratic, nonviolent, and egalitarian republic. The book recognizes that even though Costa Rica's exceptionalist rendition draws on some undeniable realities, it thoughtfully considers the origins, applicability, and longevity of the different elements of this exceptionalist master narrative. In particular, it suggests the mythology emerged during the Cold War, as revolution, civil war, military dictatorship, and state violence plagued much of Central America. In this same period, Costa Rica not only retained a relatively stable democratic system, but policymakers eliminated the standing army in 1948. This widely embraced and celebrated historical narrative, however, distorts as much as it illuminates the experience of contemporary and historical actors"–
Keywords: Coffee industry; Costa Rica; Costa Rica; History; Political aspects; dept.his